Pola Asuh dalam Al-Qur’an (Studi Atas QS. Luqman Ayat 13-19 Pada Tafsir Al-Amthal Karya Nāsir Makārim Shīrāzī) - Zilpiani; Muhammad Shodiq (AL-BAYAN INSTITUTE, 2022)
This article is a literature review on Parenting in the Qur'an (Study of QS. Luqman in Tafsir Al-Amthal by Nasir Makārim Shīrāzī). This research was raised from several social problems regarding the wrong ways or methods of parents in raising children. There are several wrong methods of parents in educating children including parents who are toxic parents, this toxic parenting pattern is a toxic parenting pattern, a different way from that taught by the Prophet Muhammad and the Qur'an or from parenting sciences in general. Parents with behavior like the above are parenting patterns that are detrimental or damaging to the emotional and mental well-being of their children. This behavior can appear in various forms, including physical, emotional, and psychological children. This paper aims to examine more deeply the concept of parenting in the Qur'an from the perspective of Nasir Makārim Shīrāzī in the current context full of challenges, the importance of guidelines on parenting in Islam, especially in the view of the Qur'an which is an urgent need. This study uses a thematic method with a social approach and descriptive-analytical research type. The results of this study indicate that Makārim Shīrāzī's interpretation of parenting is not explicitly mentioned. However, his views on parenting are taken from the principles of the Qur'an by using verses of the Qur'an to emphasize the importance of the role of parents in guiding their children through strong moral and spiritual education. Verses such as those in Surah Luqman verses 13-19, Shīrāzī in his view highlights the importance of respecting children's autonomy. Parents must understand that although they have an important role in guiding children, they must also respect children's freedom to think and act according to their own personality and needs. Respecting children's autonomy within the framework of the values ​​of the Qur'an will help children grow into independent, responsible individuals who are able to face life's challenges with confidence.